Outcomes of and factors associated with the development of bronchopulmonary dysplasia with pulmonary hypertension in very low birth weight infants: A retrospective study in a medical center - Chang, Han-Pi; Lien, Reyin; Chu, Shih-Ming; Lin, Jainn-Jim; Chiang, Ming-Chou (Frontiers in Pediatrics, 2023)
Introduction Bronchopulmonary dysplasia (BPD) with pulmonary hypertension (PH) leads to increased morbidity and mortality in extremely preterm infants. Recent studies have analyzed factors associated with development of PH in BPD; however, this research remains inconclusive, and controversy exists regarding the correlation between BPD and PH. This study aimed to investigate potential associated factors, clinical characteristics, and outcomes of BPD with pulmonary hypertension in very low birth weight (VLBW) preterm infants. Methods We conducted a retrospective study, reviewing the records of infants with gestational age (GA) <32 weeks and birth weight <1,500 g admitted to a tertiary neonatal intensive care unit between January 2020 and October 2021 who were diagnosed with moderate to severe BPD. Echocardiogram was performed at the postmenstrual age of 36 weeks or before discharge. The diagnosis of PH was based on the findings of echocardiogram. Prenatal and postnatal characteristics, demographic data, treatment details, and outcomes were collected and analyzed. Results A total of 139 VLBW infants with BPD were enrolled and divided into a PH group (n = 25) and a non-PH group (n = 114). The mean GA was 27.3 ± 2.3 weeks and the mean birth weight of infants with BPD was 927.3 ± 293.3 g. A multivariate logistic regression model revealed that a high positive end-expiratory pressure (PEEP) setting (OR: 2.105; 95% CI: 1.472–3.011; p < 0.001) in established BPD and surgical closure of patent ductus arteriosus (PDA; OR: 6.273; 95% CI: 1.574–24.977; p = 0.009) were associated with BPD–PH. Neonates with BPD who developed pulmonary hypertension remained hospitalized for longer (p < 0.001), received invasive mechanical ventilation support for longer (p < 0.001), had a higher incidence of retinopathy of prematurity (ROP; OR: 4.201; 95% CI: 1.561–11.304; p = 0.003), were more likely to require oxygen support at discharge (OR: 5.600; 95% CI: 2.175–14.416; p < 0.001), and were more likely to undergo tracheostomy (OR: 35.368; 95% CI: 4.03–310.43; p < 0.001). Conclusion PDA ligation and a higher PEEP setting were associated with BPD–PH in our cohort study. Compared with VLBW infants with BPD but without PH, infants with BPD and PH were hospitalized for longer, and also had a higher incidence of oxygen support after discharge, ROP, and tracheostomy.